Epistemologi Suatu Landasan Pengetahuan Dalam Filsafat Ilmu - Koli, Yulenni Bandora; Syukur, Muhammad (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Epistemology is a branch of philosophy that focuses on the methods of acquiring, verifying, and organizing true knowledge, which forms the foundation for the development of scientific knowledge through the scientific method. As a foundation of the philosophy of science, epistemology not only defines the characteristics of knowledge but also the criteria for truth that can be accepted systematically and objectively. This research uses a literature review method. The study aims to construct a comprehensive and in-depth theoretical framework to understand epistemology in the philosophy of science. The results show that in science, epistemology provides a strong methodological foundation by integrating rationalism and empiricism, ensuring that the knowledge produced can be logically and empirically accounted for. Various epistemological schools, such as idealism, rationalism, realism, empiricism, criticalism, positivism, and post-positivism, offer different perspectives on the sources and validity of knowledge. Epistemology not only defines the characteristics of knowledge but also sets the criteria for truth, which is crucial in establishing a valid knowledge foundation in science. In the context of education, epistemology also plays a role in developing a holistic teaching methodology, encompassing the integration of revelation, reason, and experience to form a deeper understanding